APPLICATION OF THERMAL PLASMA FOR INERTIZATION OF SLUDGE PRODUCED DURING TREATMENT OF LANDFILL LEACHATE - Cubas,Anelise Leal Vieira (2016)
One of the outstanding issues of concern by governments and society in general relates to the final destination of solid waste, which can bring severe impacts on social, political, economic and environmental dimensions. The sustainable development of enterprises and industries goes for the care of the planet, thus ensuring the quality of life for future generations and the planet. The disposal of municipal waste in landfills is the technique most commonly employed for the remediation of solid residues. The residues undergo decomposition beneath the soil and in the presence of water this generates leachate, which percolates down to the bottom of the landfill through drainage. This drained liquid is collected from the landfill installations and subjected to treatment, which involves physico-chemical and biological processes. Landfill leachate commonly contains heavy metals due to the incorrect disposal of products such as fluorescent bulbs and batteries. In this context, a method for the treatment of sludge originating from the physicochemical remediation of leachate using thermal plasma is proposed in this paper. The efficiency of the method was verified by monitoring the total organic carbon content, water content and density of the sludge. The quantity of metals present in the samples was determined before and after pyrolysis by thermal plasma using flame atomic absorption spectroscopy (FAAS), scanning electron microscopy (SEM) and X-ray fluorescence (XRF) spectrometry techniques. The results show that the leachate treatment method used was efficient, presenting the best results for the samples of iron and zinc.